Poisoning and drug overdose : by the faculty, staff and associates of the California Poison Control Systems - Olson, Kent R (Appleton & Lange, 1999)
This is the leading manual on the diagnosis and treatment of poisoning and drug overdose, including chemical and occupational exposures.
Lange clinical manual
Keywords: nežádoucí účinky léčiv; Drug-Related Side Effects and Adverse Reactions; léčivé přípravky; Pharmaceutical Preparations; farmacie a farmakologie; toxikologie; Poisoning; otrava